Sistem Informasi Pengelolan Laporan Keuangan Berbasis Web Pada CV. Damar Abadi - thahir, anna; Lisnawanty, Lisnawanty (LPPM Universitas Bina Sarana Informatika, 2024)
CV. Damar Abadi transaction data processing and financial reports still use a manual system, namely recording still uses manual writing even for writing reports recorded in the ledger. The purpose of this study is to design a web-based cash receipt and disbursement management information system using the waterfall model for software development. Data collection techniques used are observation, interviews and literature studies. This application can help CV. Damar Abadi in managing inventory data, sales and purchase transactions, to the process of making financial reports automatically. This is very helpful for the company in managing its business.